Herpes simplex virus type I glycoprotein L evades host antiviral innate immunity by abrogating the nuclear translocation of phosphorylated NF-κB sub-unit p65 - Li, Zhaolong; Feng, Zhihua; Fang, Zhou; Chen, Jianghua; Chen, Wengzhi; Liang, Wangwang; Chen, Qi (Frontiers in Microbiology, 2023)
Nuclear factor (NF)-κB plays an important role in the innate immune response by inducing antiviral genes' expression. However, the herpes simplex virus 1 (HSV-1) virus has developed multiple ways to interfere with NF-κB activity to escape the host antiviral response. Here, we found that HSV-1 envelope glycoprotein L(gL) markedly inhibits interferon (IFN) production and its downstream antiviral genes. Our results showed that ectopic expression of gL inhibited IFN-β promoter activation, and decreased IFN-β production, the expression of IFN-stimulated genes (ISGs), and inhibited immunologic stimulant (poly I:C) induced activation of IFN signaling pathway. Depletion of gL by short interfering RNA (siRNA) significantly upregulated IFN-β and ISG production. Further study showed that the N-terminus of the gL bound to the Rel homology domain (RHD) of the p65 and concealed the nuclear localization signal of p65, thereby impeding the translocation of phosphorylated p65 to the nucleus. In summary, our findings indicated that the N-terminal of HSV-1 gL contributes to immune invasion by inhibiting the nuclear translocation of p65.